Perlindungan Hukum dan Pengawasan Perawat dalam Delegasi Tindakan Medis di Rumah Sakit - Munif Amar; M. Syahrul Borman; Wahyu Prawesthi (Sanskara Hukum dan HAM, 2026)
As a healthcare institution, the hospital is mandatory to provide competent human resources, with physicians and nurses serving as the central pillars. In clinical practice, nurses no longer only provide independent nursing care but also perform medical acts through the mechanism of delegation of authority from physicians. This normative juridical research employs a deductive approach to analyze the legal provisions regarding the delegation of medical acts and to examine the aspects of supervision and legal protection for nurses. A qualitative analysis was conducted on existing regulations to map out the boundaries of authority and standard procedures within collaborative services. The research findings emphasize that professional competence is a fundamental prerequisite to ensure that delegated medical acts are performed safely and accountably. Although hospitals bear institutional responsibility, nurses still face the risk of personal liability—whether criminal, civil, or administrative—if they are proven to have performed medical acts without valid written delegation or in deviation from professional standards and applicable operating procedures. Enforcement of legal certainty within the delegation mechanism is crucial to protect the rights of nurses while simultaneously ensuring patient safety.